Inactivation of ATF‐2 enhances epithelial‐mesenchymal transition and gemcitabine sensitivity in human pancreatic cancer cells. Issue 3 (26th October 2018) - Wu, Xingda; Liu, Zhe; Guo, Kejia; Ma, Gang; Song, Shaowei
Abstract: Objective: This work aimed to study the activating transcription factor 2 or AMP‐dependent transcription factor‐2 (ATF‐2) inhibition mediated gemcitabine sensitivity in human pancreatic cancer cells. Methods: The protein and messenger RNA expressions of ATF‐2 in 42 pancreatic cancer tissues and adjacent nontumorous tissues were detected. Kaplan‐Meier survival analysis was performed based on the expression level of ATF‐2 protein in tumor tissues. Then the pancreatic cancer cells were transduced with ATF‐2‐expressing lentivirus and small interfering RNAs (siRNAs) to investigate the effect of ATF‐2 on pancreatic cancer cell invasion, epithelium to mesenchyme transition, apoptosis, and gemcitabine sensitivity. Results: The expression of phosphorylated (p)‐ATF‐2 protein was upregulated in pancreatic cancer tissues compared with adjacent nontumorous tissues. Patients with relative higher p‐ATF‐2 level showed significantly lower survival time. Then we found that the transfection ATF‐2 siRNA into BxPC3 cells inhibited cell proliferation, invasion, and epithelium to mesenchyme transition, but enhanced cell apoptosis. These changes could be enhanced by the additional administration of gemcitabine. In addition, we confirmed that the overexpression of ATF‐2 in Panc‐1 cells promoted cell invasion and epithelium to mesenchyme transition. Conclusion: We concluded that inhibition‐promoted ATF‐2 expression was responsible for epithelium to mesenchyme transition and invasion of pancreatic cancer cells, while the inhibition of ATF‐2 confers to gemcitabine sensitivity in human pancreatic cancer cells in vitro. Abstract : We concluded that inhibition promoted the activating transcription factor 2 or AMP‐dependent transcription factor‐2 (ATF‐2) expression and was responsible for epithelium to mesenchyme transition and invasion of pancreatic cancer (PCa) cells, while the inhibition of ATF‐2 confers to gemcitabine sensitivity in human PCa cells in vitro.